Genomic regions controlling shape variation in the first upper molar of the house mouse - Pallares, Luisa F (eLife, 2017)
Numerous loci of large effect have been shown to underlie phenotypic variation between species. However, loci with subtle effects are presumably more frequently involved in microevolutionary processes but have rarely been discovered. We explore the genetic basis of shape variation in the first upper molar of hybrid mice between Mus musculus musculus and M. m. domesticus. We performed the first genome-wide association study for molar shape and used 3D surface morphometrics to quantify subtle variation between individuals. We show that many loci of small effect underlie phenotypic variation, and identify five genomic regions associated with tooth shape; one region contained the gene microphthalmia-associated transcription factor Mitf that has previously been associated with tooth malformations. Using a panel of five mutant laboratory strains, we show the effect of the Mitf gene on tooth shape. This is the first report of a gene causing subtle but consistent variation in tooth shape resembling variation in nature.